Bis(phenylsulfinyl)methane - Wardell, S.M.S.V.; de Lima, G.M.; Wardell, J.L.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent molecules comprise the asymmetric unit of the title compound, C13H12O2S2, which differ in terms of minor variations in the relative orientations of the benzene rings [the O-S-C-C torsion angles for the first independent molecule are -6.66 (17) and -12.88 (19)degrees compared with -21.70 (18) and 4.83 (16)degrees for the second molecule]. Supra-molecular chains sustained by C-H center dot center dot center dot O contacts and aligned along the a axis are found in the crystal structure. These are held in place in the three dimensional structure by C-H center dot center dot center dot pi interactions.